2002
DOI: 10.15407/spqeo5.04.395
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectric properties of metal-porous silicon-silicon planar heterostructures

Abstract: Dark and light IV characteristics as well as spectral curves of planar Niporous siliconp-SiNi heterostructures have been studied. It is shown that photogeneration in heterostructure occurs both in the region of thin porous silicon layer and p-Si base. Avalanche breakdown is observed in the heterostructure at applied voltage biases V > 810 V and T = 77 K. The coefficient of multiplying at V = 11 V achieves 60 (dark) and 200 (light), which is close to that of silicon n +-p-i-p + avalanche photodiodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
1
1
0
Order By: Relevance
“…Further observation revealed that the light responsivity is reduced sharply at smaller wavelength (blue and near UV). This is confirmed by the absorption of photons in the PSi film, negating its arrival at the depletion region [9], which is consistent with other reports [35].…”
Section: Photocurrent and Light Responsivitysupporting
confidence: 93%
“…Further observation revealed that the light responsivity is reduced sharply at smaller wavelength (blue and near UV). This is confirmed by the absorption of photons in the PSi film, negating its arrival at the depletion region [9], which is consistent with other reports [35].…”
Section: Photocurrent and Light Responsivitysupporting
confidence: 93%
“…Porous silicon (PS) attracts attention of researchers because of its wide range of possible applications [1,2]. Due to its antireflective properties, a large area of absorbing surface, the increased width of the band gap of silicon nanocrystals there are interesting perspectives of application of PS in photoelectronics [3][4][5][6][7]. It has been also found that adsorption of chemically active or polar molecules causes a significant change in the concentration of free charge carriers in the PS and its electrophysical parameters [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%